Pengaruh Semangat Kerja Terhadap Kinerja Pegawai Pada Kantor Distrik Navigasi Kelas II Teluk Bayur - Husna, Nikmatul (CV. ITTC INDONESIA, 2022)
This study entitled The Influence of Work Morale on Employee Performance at the Class II Navigation District Office of Teluk Bayur. The purpose of this study was to identify and analyze the influence of morale on employee performance at the Teluk Bayur Class II Navigation District Office. The population in this study were employees in the Teluk Bayur Class II Navigation District office, namely 147 people. Samples were taken as many as 50 respondents using purposive sampling technique. Based on the hypothesis in this study, it is assumed that there is an influence of morale on employee performance at the Teluk Bayur Class II Navigation District Office.The data analysis method that the authors used in this research was validity test, reliability test, variable descriptive analysis test, simple linear regression analysis, T test and F test. positive effect on employee performance, this is evidenced by the significant probability value of morale producing 0.003 which is smaller than 0.05. From the F test it can be concluded that the regression model can be used to predict morale which has a positive and significant effect on employee performance with a significant probability value producing 0.003 which is smaller than 0.05.